Characterisation of the anabolic effects of leucine on primary chicken muscle cells and murine C2C12 muscle cells - Elsaied, Nashwa (2021)
Leucine is a branched-chain amino acid, which possesses a unique ability to stimulate the rate of protein synthesis in muscle cells both in vivo and in vitro. This thesis aimed to evaluate the anabolic effects of leucine on primary chicken and continuous murine muscle cells.This thesis elucidated the differences between satellite cells derived from chickens selected for high growth (broilers) and chickens with normal growth rate (layers). It also elucidates the differences that exist between satellite cells derived from selected (breast) and unselected (leg) muscles of the same bird. The results of this thesis suggest that leg deformities in modern broiler chickens could be due to poor proliferation and differentiation of leg muscle cells. They also suggest that leucine supplementation may provide added benefit in increasing the mass and strength of broilers leg muscles. This thesis has also shown the negative effects associated with serum restriction and emphasised the central role of serum in promoting the protein effects of leucine on cultured muscle cells. New insights into the concentration- and time-effects of leucine on C2C12 cells have been provided. In addition, this thesis elucidated how the combined effect of leucine and glutamine is both concentration- and time-dependent. Moreover, a possible involvement of signalling pathways, other than mTOR, in mediating the protein effects of leucine on muscle cells was detected. Finally, this thesis has been the first to test the temporal expression of myomiRs in cultured muscle cells following leucine treatment. It is hoped that these findings may ultimately contribute to the development of a nutritional strategy, using leucine, to increase muscle mass and subsequently improve the health and welfare of broiler chickens and mitigate muscle wasting in humans.